The Noumenon's New Clothes (Part 1) - Peter Wolfendale (Speculations 3, 2012)
A spectre is haunting conti-nental philosophy—the spectre of Object-Oriented Ontology(OOO). All the disciplines and groupings that have traditionally allied themselves with continental theory in the anglophone world are poised to greet its manifestation: aesthetic theory and artistic practice, political philosophy and heterodox ge-ography, Francophile post-post-structuralists and Germanist neo-romantics. Who among them has not heard the siren song of OOO’s litanies of inhuman objects (menageries of stock markets and stock cubes, quarks and clerks, etc.)? Who among them has not begun to shrug off the oppressive, anthropocentric legacy of Post-Kantian philosophy, bravely railing against the tyrannical correlationists of the continental academy, the dreary technicians of the analytic mainstream, and even the scientistic fury of its Neo-Kantian heirs?